2017
DOI: 10.1002/mnfr.201700294
|View full text |Cite
|
Sign up to set email alerts
|

Blood–Brain Barrier Permeability of Green Tea Catechin Metabolites and their Neuritogenic Activity in Human Neuroblastoma SH‐SY5Y Cells

Abstract: The permeability of EGC-M5 and its conjugated forms into the BBB suggests that they reached the brain parenchyma. In addition, the ability of EGC-M5 to affect nerve cell proliferation and neuritogenesis suggests that EGC-M5 may promote neurogenesis in the brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
92
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 102 publications
(93 citation statements)
references
References 20 publications
0
92
0
1
Order By: Relevance
“…34 Human and animal studies have observed markers of decreased oxidative stress in response to EGC gallate and EGC supplementation, and several studies have demonstrated that EGC and its derivatives can penetrate the blood brain barrier and enter the brain parenchyma. [35][36][37][38] Taken together, this evidence suggests that EGC gallate may possibly play a role in reducing the burden of neurodegenerative diseases. 38 These mechanisms could also explain the decreased glioma risk associated with tea consumption observed in this study.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…34 Human and animal studies have observed markers of decreased oxidative stress in response to EGC gallate and EGC supplementation, and several studies have demonstrated that EGC and its derivatives can penetrate the blood brain barrier and enter the brain parenchyma. [35][36][37][38] Taken together, this evidence suggests that EGC gallate may possibly play a role in reducing the burden of neurodegenerative diseases. 38 These mechanisms could also explain the decreased glioma risk associated with tea consumption observed in this study.…”
Section: Discussionmentioning
confidence: 72%
“…In vitro , EGC gallate and EGC can suppress breast cancer cell growth via induction of apoptosis . Human and animal studies have observed markers of decreased oxidative stress in response to EGC gallate and EGC supplementation, and several studies have demonstrated that EGC and its derivatives can penetrate the blood brain barrier and enter the brain parenchyma . Taken together, this evidence suggests that EGC gallate may possibly play a role in reducing the burden of neurodegenerative diseases .…”
Section: Discussionmentioning
confidence: 85%
“…Plasma metabolites including conjugates, were characterized and identified from precursor MS ion and MS n fragmentation. [31][32][33] Glucronide form of EGC-M5 (EGC-M5-GluUA) and sulfate form of EGC-M5 (EGC-M5-Sul) were prepared according to the previously reported method. 32) LC/MS/MS analysis for quantification of plasma metabolites was conducted according to the procedure described in previous reports.…”
Section: Quantitative Analysis Of Plasma Metabolites After Oral Adminmentioning
confidence: 99%
“…An important issue not addressed in the present study regards the ability of the tested PVLs to cross the blood–brain barrier (BBB). We note, however, that different PVLs scored positive in artificial BBB model systems, where 5‐(3′,4′‐dihydroxyphenyl)‐γ‐valerolactone (#2) and 5‐(4′ hydroxyphenyl)‐γ‐valerolactone‐3′‐sulfate (#5) displayed high penetration capacities. Although brain PVL levels are difficult to predict, the bioavailability and prevalence of PVLs as long‐lasting flavan‐3‐ol metabolites (elimination half‐life ≈6 h) along with their sub‐micromolar peak plasma concentrations (>500 n m ) suggest that potentially effective, cumulative brain PVL levels might be reached, at least in response to a flavan‐3‐ol rich diet.…”
Section: Discussionmentioning
confidence: 99%
“…Additional biological activities of PVLs, some of which may be relevant to their ability to relieve A O-induced memory impairment and neuroinflammation, have been reported previously. [18] These include pro-neuritogenic, [48] anti-inflammatory, [49] and antioxidant activities. [50] The existence of a positive correlation between intake of flavan-3-ol rich foods (especially cocoa [15,16] ) and cognitive performance has also been documented.…”
Section: Discussionmentioning
confidence: 99%